Measurement methods of torsional vibration of ships propulsion system [electronic resource] - Tan, Ji Sing, 1989-; Nasrudin Ismail; Fakulti Kejuruteraan Mekanikal (2013)
Project Paper (Sarjana Muda (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2013